The ASCRS Textbook of Colon and Rectal Surgery - Steele, Scott R.; Hull, Tracy L.; Read, Thomas E.; Saclarides, Theodore J.; Senagore, Anthony J.; Whitlow, Charles B. (Springer, 2018)
The field of Colon and Rectal Surgery has a long and respected tradition of patient service, knowledge expansion, and education. The American Society of Colon and Rectal Surgeons (ASCRS) is the premier professional organization of this specialty. The leaders of our Society (ASCRS) recognized that there were several textbooks in the field of Colorectal Surgery, but none of which could be deemed as truly representative of the collective objective views of the ASCRS. At the inaugural meeting of the senior and associate editors, prior to the 2007 publication of the ASCRS Textbook of Colon and Rectal Surgery 1st edition, the group made several fundamental decisions. One of those decisions was to have chapters extensively referenced, authoritatively written, appropriately illustrated, and as unbiased as possible. This very important latter point was strictly enforced by adherence by the chapter authors to ASCRS materials including the evidence-based ASCRS clinical practice guidelines, core subjects, presentations at our annual meeting, questions in the colon and rectal self-assessment program (CARSEP), and material otherwise presented through official society vehicles. In addition, first edition chapters were, in general, written by a “junior” and a “senior” coauthor. A second decision was a rotation schedule for the editors: two to three of the editors would rotate off after each edition. This would provide wider participation and ensure that the text would represent the specialty as a whole and not a select group of individuals. The overwhelming success of the first edition led to the publication of a second edition in 2011. The second edition expanded upon the first edition, added new authors, supplemented a significant number of color plates, and increased the text itself from 810 to 946 pages. The vision provided by the leaders of our Society was certainly correct, as attested to by the tremendous interest in both editions of the ASCRS textbooks. We are proud that the standardized reference for evidence-based material in Colorectal Surgery is the work product of our Society members, owned by our Society, and has become a source of financial support to our Society. In addition, a corresponding manual (the ASCRS Manual of Colon and Rectal Surgery), designed more towards residents in training and physicians desiring a focused reference, has been released for each edition and has also been exceptionally popular. The continued rapid expansion of knowledge, in part attested by the increased number of pages in each subsequent edition, as well as the new technologies and new techniques has ensured the longevity of our work and has necessitated this third edition. We congratulate the current editors Drs. Scott Steele, Tracy Hull, Thomas Read, Anthony Senagore, Theodore Sacclarides, and Charles Whitlow on their tremendous accomplishment. We also thank all of the chapter authors and coauthors whose dedication, devotion, energy, and expertise have enabled the editors to produce this volume. The third edition has been reorganized and completely rewritten to reflect advances in our specialty and the evolution of our practice. In addition, the current grouping of topics serves as a framework for the ongoing educational efforts of the Society and certification process by the American Board of Colon and Rectal Surgery.